A new theory of essential hypertension based on analysis of the association between a polymorphism of the α2-adrenoceptor at the 10q24–q26 locus and hypertension in African-Americans. Issue 5 (November 2015) - Eggers, Arnold E.
Abstract Some key historical observations about essential hypertension (HTN) are reviewed, analyzed logically, and used to construct a new theory of hypertension. The historical observations are as follows: Lockette reported a statistical association between HTN in African-Americans and the 6.3-kb allele of a restriction fragment-length polymorphism of the gene for the α2-adrenoceptor, which is found on platelets. Individuals carrying at least one copy of the 6.3-kb allele had increased in vitro epinephrine-induced platelet aggregation. Systemic or blood-wide platelet activation (SPA) induced by epinephrine has been shown to be an in vivo feature of HTN, and serotonin and thromboxane A2, two vasoconstrictors released by activated platelets, synergize in vitro with angiotensin II. Esler showed that there is increased noradrenergic drive in the heart and kidney in HTN, although renin levels are usually normal. Mulvany's group showed that small arteries controlling vascular resistance undergo remodeling in HTN. Putting together these observations leads to the following theory. Essential HTN is a disease in which the brainstem set point for blood pressure (BP) is reset, which causes the autonomic nervous system to release increased norepinephrine in the heart and kidney and increased epinephrine from the adrenal medulla. Epinephrine release causes SPA. In the first stage of the disease, when renin is high, serotonin and thromboxane A2 released by activated platelets synergize with high angiotensin II to raise BP. Rising BP causes vascular remodeling, a structural attempt at autoregulation of blood flow which maintains normal flow artery-by-artery but has the side-effect of increasing total peripheral resistance (TPR), even beyond that caused by high renin. The presence of ever rising TPR and, therefore, ever rising BP, gradually overcomes the effect of noradrenergic drive in the kidney and leads to suppression of renin release by the juxtaglomerular apparatus. Renin levels fall pari passu with rising TPR caused by vascular remodeling. In the second stage of the disease, when renin has fallen back to normal (or low), increased TPR caused by vascular remodeling persists as a factor raising BP.